1973
DOI: 10.1507/endocrj1954.20.135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-5-HTP on the Release of Growth Hormone, TSH and Insulin

Abstract: Effect of L-5-HTP (L-5-hydroxytryptophane) on the release of human growth hormone (HGH), thyroid stimulating hormone (TSH) and immunoreactive insulin (IRI) was investigated in 7 normal subjects and 25 patients with endocrine disorders. A single oral dose of 200mg of L-5-HTP showed the elevation of HGH in plasma; however, no release of TSH and insulin in plasma of normal subjects. HGH response to L-5-HTP administration was less in quantity as compared with HGH respone to insulin hypoglycemia or arginine infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…These data are further consistent with the lack of effect of the 5-HT receptor antagonist metergoline on basal and TRH-stimulated TSH in normal men [10], However, they may not be inconsistent with data from 5-HTP studies which suggest an inhibitory effect of 5-HT on TSH in pa tients with primary hypothyroidism [16,40]. It is possible that central 5-HT receptors may be supersensitive in the hypothyroid state secondary to decreased 5-HT synthesis and turnover [35].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These data are further consistent with the lack of effect of the 5-HT receptor antagonist metergoline on basal and TRH-stimulated TSH in normal men [10], However, they may not be inconsistent with data from 5-HTP studies which suggest an inhibitory effect of 5-HT on TSH in pa tients with primary hypothyroidism [16,40]. It is possible that central 5-HT receptors may be supersensitive in the hypothyroid state secondary to decreased 5-HT synthesis and turnover [35].…”
Section: Discussionsupporting
confidence: 77%
“…Transient stimulation, followed by prolonged suppression, of plasma TSH during 5-HTP infu sion has been reported in one study [21], Data from similar studies employing 5-HTP, however, suggest and inhibitory effect of 5-HT on TSH in patients with primary hypothyroiReceived; October 24. 1986 Accepted after revision: September 4, 1987 dism [16,40], Finally, no effect of 5-HT on TSH has been suggested by studies examining the effect of metergoline, a 5-HT receptor antagonist, on basal TSH and TSH induced by thyrotropin-releasing hormone (TRH) [10] or of acute or subchronic treatment with the 5-HT reuptake inhibitor zimelidine on basal levels of TSH [26].…”
mentioning
confidence: 99%
“…Most studies support the idea of the hypothalamic noradrenergic stimulation and dopaminergic inhibition of TSH secretion [19], The role of 5-hydroxytryptamine (5-HT) has been most controversial and the results published so far have suggested either no effect [32], a definite inhibition [5,14,18] or stimulation [4,9] of TSH secre tion.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the discrepancy between our and their data is not readily apparent. However, the fact that both Yoshimura et al (1973) and Takahashi et al (1973) also observed stimulatory effect of 5-HTP on plasma hGH suggests that the discrepancy seems to be attributed at least partly to the differences of the races or the drugs used.…”
Section: Discussionmentioning
confidence: 93%